Strategi Pengembangan Usaha Pembenihan Udang Skala Rumah Tangga Melalui Pendekatan Agribisnis Di Kecamatan Tonra, Kabupaten Bone - Yusnan Suyuti DM (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
Household scale shrimp hatchery is a type of business Small-scale shrimp hatcheries by utilizing home yards or narrow land as business locations and can be carried out by families with family members as executing staff (Sutaman, 1993). Household scale hatchery is a hatchery business using simple technology, small capital, location around the house and its activities are only part of a series of shrimp hatcheries with an agribusiness approach. A complete concept, starting and processing of production, processing, marketing and other activities related to agricultural activities (Soekartawi, 2003). The successful implementation of the agribusiness system cannot be separated from the availability of natural resources (SDA) and human resources (HR). This study uses a SWOT analysis comparing external factors, opportunities and threats with internal factors, strengths and weaknesses. The increasingly tight competition situation demands that small and medium industries have to equip themselves with the strengths that can place their products to be able to compete with other similar products. Their strength is expected to be a competitive advantage in domestic and foreign markets.